Growth hormone attenuates obesity and reshapes gut microbiota in high-fat diet-fed mice - Yu Wang; Liyuan Ran; Fang Zhang; Haolin Li; Qianqian Cha; Kun Yang; Haoan Wang; Yingjie Wu; Zichao Yu (Metabolism Open)
Growth hormone (GH) and gut microbiota are key regulators of metabolism and have been linked to the development and treatment of obesity. Although variations in GH levels are associated with changes in gut microbiota composition, the specific effects of GH on gut microbiota and its role in obesity remain unclear. This study explored the effects of various GH doses (0.25, 0.75 and 1.5 IU/kg) on adipose tissue mass and gut microbiota in high-fat diet-induced obese mice. Notably, high-dose GH (1.5 IU/kg) significantly reduced the adipose tissue mass. This dose also reversed high-fat diet-induced gut microbiota dysbiosis, restoring microbial diversity and increasing the abundance of beneficial genera such as Ruminococcaceae and Muribaculaceae. Additionally, high-dose GH normalized several obesity-related gut microbiota pathways, including starch and sucrose metabolism, galactose metabolism, and secondary bile acid biosynthesis. GH therapy also improved intestinal barrier function, a key determinant of gut microbial homeostasis. These findings underscore the therapeutic potential of GH in obesity management through its effects on gut microbiota, providing new avenues for obesity interventions.